Laser polishing device and debugging method thereof for high-brightness polishing of aluminum alloy
Patent Information
- Application Number
- CN202510232589.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-02-28
AI Technical Summary
通过对其结构和参数进行复现表明:①激光镭雕后所能达到的表面粗糙度(0.6um)和亮度指标较低(200GU);②整个工艺缺乏数据分析、优化过程;③工艺过程具有较大的不确定性;④尤其是更换材料时,不能快速找到窗口参数,需要较长时间的摸索,不利于产品的快速切换
Smart Images

Figure CN120023477B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of laser polishing technology, and in particular to a laser polishing apparatus and a method for adjusting it for high-gloss polishing of aluminum alloys. Background Technology
[0002] Aluminum alloys possess advantages such as high strength, light weight, good electrical and thermal conductivity, excellent processing performance, good coloring properties, and the formation of a wear-resistant surface layer after anodizing. They are widely used in construction, transportation, aerospace, medical, 3C (computers, communications, and consumer electronics) and electronic products. As a high-quality material for structural and aesthetic components, aluminum alloys offer a wide variety of structures, diverse processing methods, and colorful appearances. Combined with exquisite logos and surface decorative patterns, they can further enhance the product's grade and brand recognition.
[0003] While printing logos is simple, its ease of erasure limits its lifespan. Logo mounting is complex, requiring various auxiliary equipment and processes, resulting in higher costs. Sandblasting logos require creating different templates and can only be completed before anodizing, leading to significant uncertainty in the final result, making it unsuitable for small-batch, multi-variety production, customized complex designs, and rapid product iteration. Laser engraving of logos and surface decorations offers convenience and flexibility, enabling the processing of complex patterns even after anodizing, making it an excellent solution.
[0004] In recent years, laser high-gloss polishing has become popular and has been widely adopted by many manufacturers and for various products, such as DELL laptops, Samsung mobile phones, and e-cigarettes. However, with the increasing demands for product technology and customer experience, the original polishing effect can no longer meet the requirements in terms of both fineness and brightness. For example, Chinese patent CN113458611 A discloses a laser marking method and device for high-gloss processing of aluminum alloys, which is actually a common application of laser marking machines. Its output conclusions are qualitative rather than quantitative. Reproduction of its structure and parameters shows that: ① the surface roughness (0.6um) and brightness index (200GU) achievable after laser engraving are relatively low; ② the entire process lacks data analysis and optimization; ③ the process has significant uncertainties; ④ especially when changing materials, it is not possible to quickly find the window parameters, requiring a long period of exploration, which is not conducive to rapid product switching. Summary of the Invention
[0005] The main objectives of the laser polishing device and its debugging method of the present invention are twofold: first, to use laser scanning to remove the anodic oxide layer on the surface of aluminum alloy, expose the aluminum material body, and reduce the surface roughness of the aluminum material body; and second, to scan a higher brightness on an aluminum material body with a lower surface roughness.
[0006] To achieve the above objectives, this invention provides a laser polishing device for reducing the surface roughness of aluminum alloys after laser polishing and improving the polishing brightness, as well as a high-brightness polishing debugging method that adapts to rapid switching of various aluminum alloy materials. It has strong logic and reproducibility. The laser polishing device, combined with its debugging method, can reduce the surface roughness of aluminum alloys after high-brightness laser polishing to below 0.4 μm and increase the polishing brightness to 400-650 GU. The specific implementation scheme is as follows.
[0007] A laser polishing apparatus is provided, comprising a fiber laser, a lifting mechanism, a laser processing assembly, and a processing platform. The laser processing assembly includes a laser output head, a beam expander, a dot-of-extension (DOE), and a galvanometer assembly. The fiber laser can be modulated into both pulsed and continuous laser modes, and outputs Gaussian laser light from the laser output head. The Gaussian laser light is expanded, shaped, and scanned and focused sequentially by the beam expander, DOE, and galvanometer assembly before irradiating the processing platform. The laser processing assembly is mounted on the lifting mechanism, which is used to adjust the vertical movement of the laser processing assembly. The processing platform is located below the galvanometer assembly.
[0008] Furthermore, the fiber laser is a fiber infrared MOPA single-mode laser. In some specific embodiments, the fiber laser is a 50-500W fiber laser, preferably a 200W fiber laser, but not limited to 200W.
[0009] In some specific embodiments, the focal length of the galvanometer is 100-260mm, such as commonly used 100mm, 160mm, 200mm, 254mm, etc., with a preferred focal length of 160mm.
[0010] Furthermore, the laser polishing device also includes a base; the lifting mechanism and processing platform are mounted on the base.
[0011] The above-mentioned laser polishing device for high-gloss polishing of aluminum alloys is characterized by the following steps: Step 1: Removing the anodized layer
[0012] Step 11: Detect the oxide layer thickness;
[0013] Step 12: Determine the parameters of the anode-breaking laser.
[0014] S121 Focusing: Place the aluminum alloy sample on the processing platform and adjust the lifting mechanism to move the laser processing component to the front focal coordinate or the rear focal coordinate.
[0015] S122 Frequency Setting: Refer to the waveform diagram of the laser and set the frequency F corresponding to the highest power.
[0016] S123 Pulse Width Setting: Refer to the laser parameter table to set the pulse width PW corresponding to the frequency F;
[0017] S124 scribing: Set the scanning speed to any value between 100-500mm / s, and then set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, and 100% in sequence, scribing 20 lines;
[0018] S125 Inspection: Measure the line width and depth of each engraving line in sequence;
[0019] S126 Determine line width and power: First, screen out lines whose width no longer changes and have no heat-affected zone. Then, screen out lines whose depth just exceeds the oxide layer thickness. The line width and power corresponding to this line are the optimal line width D1 and power W1.
[0020] Step 13 Determine scanning parameters
[0021] S131 Determine the fill spacing: Determine the fill spacing as D1 / 2;
[0022] S132 Determine the scanning speed: Let the spot diameter be D1, the laser frequency be F, the scanning speed be V, and the overlap rate be R; the overlap rate R = 1 - V / D1 * F, take R ≥ 80%, and determine the scanning speed V = (1 - R) * D1 * F by calculation;
[0023] S133 determines the switch optical delay: the switch optical delay setting value is 0-100ms;
[0024] S134 Define the fill pattern: Select parallel line fill;
[0025] S135 determines the fill direction: Select 0 degrees, bow-shaped fill;
[0026] S136 Sample Fabrication: According to the parameters set in S131-S136, fabricate several 25*25mm samples for the next step, Step 14, testing.
[0027] Step 14 Second Scan
[0028] S141 Determine the secondary scan linewidth and power: Keeping other parameters unchanged, set the filling distance to D1 / 2, D1 / 2±0.005mm, D1 / 2±0.01mm, and D1 / 2±0.015mm respectively, the laser power to W1 / 2, W1 / 2±5%, and W1 / 2±10%, the filling direction to 90 degrees, and the filling in an arc shape. Take a sample from S136 and make a 5*5mm sample on it. Use a microscope to check the roughness of the sample and determine that the filling distance corresponding to the sample with the lowest roughness is the secondary scan linewidth D2 and the corresponding laser power is the secondary scan power W2.
[0029] S142 Sample Fabrication: Based on the secondary scan line width D2 and secondary scan power W2 parameters determined in S141, perform secondary scanning on the remaining samples obtained in S136 to fabricate 25*25mm samples for the next step Step2 test.
[0030] Step 2: Aluminum Material Planarization
[0031] S21 focuses; adjust the lifting mechanism to move the laser processing component to the exact midpoint between the front and rear focal coordinates;
[0032] S22 Grating: Set the pulse width of the fiber laser to 1ns, continuous laser mode; set the scanning speed to any value between 100-500mm / s, and then set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% in sequence, 20 graffito lines will be etched;
[0033] S23 Inspection: Measure the line width and depth of each engraving line in sequence;
[0034] S24 Initial determination of line width and power: Select lines where all the lines are melted, the width no longer increases, and there is no heat-affected zone. Then, select lines with smooth surfaces and no burst points. The line width and power corresponding to these lines are the initial determination of line width D and power W.
[0035] S25 Making a small sample: Keep the scanning speed set in step S22 unchanged, set the fill spacing to D, D / 2±0.005mm, D / 2±0.01mm, D / 2±0.015mm, and the power to W, W±5% and W±10%, respectively, and set the fill mode to grid. Make a 5*5mm small sample on the sample obtained in S142.
[0036] S26 Confirmation parameters: Use a confocal microscope to examine the samples and select the sample with the lowest roughness. The corresponding filling spacing and power parameters are the optimal parameters D3 and W3.
[0037] S27 Sample Fabrication: Based on the optimal parameters D3 and W3 confirmed in S26, fabricate a 25*25mm aluminum flattening sample on the remaining samples obtained in S142 for the next step, Step 3 test.
[0038] Step 3: Laser High-Gloss Polishing
[0039] S31 Focusing: Take a sample of S27 and place it on the processing platform. Adjust the lifting mechanism to move the laser processing component to the front focal coordinate or the rear focal coordinate.
[0040] S32 Polishing: Set the pulse width to PW, the scanning speed to any value between 100-500mm / s, the fill spacing to D1 / 2, the fill pattern to bow-shaped, and the fill direction to 0 degrees; sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or until the scanning burst point, and sequentially produce ≤20 5*5 polishing samples;
[0041] S33 testing:
[0042] S331 Observation: Observe and examine the samples using a confocal microscope, and select several samples with relatively low roughness.
[0043] S332 Gloss Measurement: Use a gloss meter to measure the selected samples above. The power corresponding to the sample with the highest GU value is the optimal first polishing power W4.
[0044] S34 Sample Fabrication: Take multiple S27 samples, set the power to W4, and keep other parameters the same as in step S32. Fabricate 25*25mm sample pieces on the S27 samples.
[0045] S35 Second Polishing: Set the scanning speed to be the same as in step S32, and the filling distances to D1 / 2, D1 / 2±0.005mm, D1 / 2±0.01mm, and D1 / 2±0.015mm respectively. The filling pattern is bow-shaped, the filling direction is 90 degrees, and the power is 2*W4, 2*W4±5%, and 2*W4±10% respectively. Make 5*5mm polishing samples on the intermediate sample in sequence.
[0046] S36 Confirmation Parameters:
[0047] S361 Observation: Observe and examine the polished samples using a confocal microscope, and select several samples with relatively low roughness.
[0048] S362 Gloss Measurement: Use a gloss meter to measure the selected samples above. The fill distance and power corresponding to the sample with the highest GU value are the optimal fill distance parameter D5 and the optimal power parameter W5.
[0049] S37 Sample Production: Produce multiple standard samples following the entire process described in S11-S36 above, check the reproducibility of parameters, and archive the samples.
[0050] Preferably, Step 11, which involves detecting the oxide layer thickness, specifically involves using an eddy current film thickness tester to detect the oxide layer thickness. There are at least five detection points, which are distributed around the periphery and center of the workpiece. The maximum detected thickness is taken as the oxide layer thickness.
[0051] Preferably, in Step 21, adjusting the lifting mechanism to move the laser processing assembly to the front focal coordinate or the rear focal coordinate specifically includes: setting the scanning speed of the fiber laser to any value between 1 and 10 mm / s, emitting laser for continuous scanning, and simultaneously adjusting the lifting mechanism to drive the laser processing assembly to continuously descend from the highest position, recording the coordinate point of the laser processing assembly when the first flash of the laser on the sample is the strongest as the rear focal coordinate, and recording the coordinate point of the laser processing assembly when the second flash of the laser on the sample is the strongest as the front focal coordinate.
[0052] Preferably, in S26, before using a confocal microscope to inspect the small sample, the method further includes using a multimeter range to test for short circuits, and the small sample is qualified if it emits a "beep" sound.
[0053] Preferably, after S362, the method further includes S363 short circuit testing: using a multimeter range, the small sample is qualified when the resistance of the small sample is infinite and no "beep" sound is emitted.
[0054] In the above debugging method of the present invention, first, the anodized layer is removed by pulsed laser scanning, the line width, depth and heat affected zone of the removed anodized layer are controlled to expose the aluminum material body; then, the low-power continuous laser homogenized by DOE is used to scan the aluminum material body with the oxide layer removed, so as to obtain a lower surface roughness; finally, the non-DOE homogenized high-power continuous laser is used for scanning, so that the tiny bumps and hollows on the surface of the base material are melted and leveled, and an oxidation reaction occurs again to form a high-brightness oxide layer surface.
[0055] The laser polishing device and the debugging method thereof of the present invention are mainly applied to the surface polishing of anodized aluminum alloys. The applicable alloy materials include 1-series pure aluminum series, 5-series aluminum-magnesium alloy series, 6-series aluminum-magnesium-silicon alloy series, and 7-series aluminum-zinc alloy series; the applicable surface polishing includes untreated surfaces and anodized surfaces, and the anodized surfaces further include natural color anodizing, black anodizing, color anodizing, sandblasting anodizing, hard low-temperature anodizing, etc., which are applicable to most aluminum alloy appearance products on the market. This debugging method is suitable for switching production between the above different alloy materials, and can quickly find out the polishing process window parameters of the alloy materials, so that the roughness of the polished surface of the alloy material can reach below 0.4um, and the surface finish can reach above 400GU, which is far higher than the highest brightness level on the current market. Brief Description of the Drawings
[0056] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without any creative effort.
[0057] Figure 1 This is a schematic diagram of the laser polishing apparatus according to an embodiment of the present invention.
[0058] Figure 2 This is a schematic diagram illustrating the working mode principle of the DOE element in an embodiment of the present invention.
[0059] Figure 3 This is a process diagram illustrating the method for adjusting the high-gloss polishing of aluminum alloys using a laser polishing device according to an embodiment of the present invention.
[0060] Figure 4 This is a process flow diagram of Step 1 of the present invention for removing the anodic oxide layer.
[0061] Figure 5 This is a process flow diagram of the aluminum material planarization process in Step 2 of this embodiment of the invention.
[0062] Figure 6 This is a process flow diagram of laser high-brightness polishing in Step 3 of this embodiment of the invention.
[0063] Figure 7 The images show the polishing effect of the laser polishing device under different adjustment parameters according to an embodiment of the present invention.
[0064] Explanation of the markings in the image:
[0065] 10-Marble base, 11-Processing platform, 12-Aluminum alloy sample, 20-Laser processing assembly, 21-Fiber laser, 22-Laser output head, 23-Beam expander, 24-Lifting mechanism, 25-DOE, 26-Galvanometer assembly, 100-Gaussian laser, 101-Gaussian laser, 102-Flat-top laser, 103-Processing beam. Detailed Implementation
[0066] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0067] Example
[0068] Please see Figure 1 The laser polishing device shown includes a marble base 10, a processing platform 11, an aluminum alloy sample 12, a fiber laser 21, a laser output head 22, a beam expander 23, a lifting mechanism 24, a DOE 25, and a galvanometer assembly 26; the laser output head 22, the beam expander 23, the DOE 25, and the galvanometer assembly 26 together form a laser processing assembly 20.
[0069] The fiber laser 21 is a 200W fiber infrared MOPA single-mode laser, modulated into both pulsed and continuous laser modes. It outputs Gaussian laser light through the laser output head 22. The Gaussian laser 100 output from the laser output head 22 is expanded by the beam expander 23 into a Gaussian laser 101 with a larger beam diameter and lower power density to reduce damage to the DOE 25. After passing through the DOE 25, the Gaussian laser 101 is shaped into a flat-top laser 102 with uniform energy. The flat-top laser 102 is then scanned and focused by the galvanometer assembly 26 to output a processing beam 103 with extremely high energy density. This processing beam 103 can be used to process various patterns on aluminum alloy surfaces. In this embodiment, the focal length of the galvanometer is 160mm.
[0070] The laser processing component 20 is mounted on the lifting mechanism 24, which can adjust the laser processing component 20 to move up and down along the Z-axis to adjust the vertical position of the focal plane and the homogenization surface, ensuring that the processing surface is located on the surface of the aluminum alloy sample 12. Both the lifting mechanism 24 and the processing platform 11 are fixedly mounted on the marble base 10, with the processing platform 11 located below the galvanometer assembly 26.
[0071] The working principle of DOE components is as follows: Figure 2 As shown, Figure 2 In the diagram, 1 represents the front focal point of the DOE, 3 represents the rear focal point of the DOE, and 2 represents the homogenization surface of the DOE. This embodiment of the laser polishing device utilizes two working modes for the DOE element: homogenization and focusing (either front or rear focal point). The laser processing component 20 is moved to the homogenization surface and the focusing point (either front or rear focal point) by the lifting mechanism 24. Specifically, the fiber laser is set to a scanning speed of 10 mm / s and emits laser light for continuous scanning. Simultaneously, the lifting mechanism is adjusted to continuously lower the laser processing component from its highest position. The coordinates of the laser processing component at the moment of the first intense flash on the sample are recorded as the rear focal point coordinates, and the coordinates of the laser processing component at the moment of the second intense flash on the sample are recorded as the front focal point coordinates. The position between the rear and front focal point coordinates is the homogenization surface.
[0072] The adjustment method for the above-mentioned laser polishing device to perform high-gloss polishing of aluminum alloys (5-series aluminum-magnesium alloys) is as follows: Figure 3 As shown, it consists of three main steps.
[0073] Step 1: Remove the anodized layer;
[0074] Step 2: Planarize the aluminum material;
[0075] Step 3: Laser high-gloss polishing.
[0076] The specific implementation steps are as follows:
[0077] Step 1 involves removing the anodized layer; the process flow is as follows: Figure 4 As shown:
[0078] Step 11: Oxide layer thickness test: The oxide layer thickness was tested using an eddy current film thickness tester. Five test points were set up around the workpiece and at the center. The maximum value was taken as the oxide layer thickness. The measured oxide layer thickness was 0.009 mm.
[0079] Step 12: Determine the parameters for the anode-breaking laser:
[0080] S121 Focusing: Take an aluminum alloy sample 12 and place it on the processing platform 11. Set the scanning speed to 10mm / s, draw a set of line segments for continuous scanning, and adjust the lifting mechanism 24 to move the laser processing component 20 to the back focal coordinate Z1.
[0081] S122 Frequency Setting: Refer to the waveform diagram of the fiber laser and set the frequency F (60KHz) corresponding to the highest power.
[0082] S123 Pulse Width Setting: Refer to the fiber laser parameter table to set the pulse width PW (100ns) corresponding to this frequency.
[0083] S124 Grating: Set the scanning speed to 500 mm / s, then sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, and 100%. 20 gradations are made. S125 Inspection: Use a confocal microscope to sequentially measure the line width and depth of each gradation.
[0084] S126 Determines line width and power: (As laser power increases, the line width gradually increases from shallow to deep. When the laser power exceeds a certain value, the line width no longer changes with increasing power.) First, screen out lines whose line width no longer changes and which have no heat-affected zone. Then, screen out lines whose line depth just exceeds the oxide layer thickness. The line width and power corresponding to this line are the optimal line width D1 and power W1, where D1 is 0.04 mm and W1 is 25%.
[0085] Step 13 Determine scanning parameters
[0086] S131 determines the fill spacing: The fill spacing is set to D1 / 2, which is 0.02mm. (When the fill spacing equals the line width, it is a window parameter. At this time, the bottom residue is a sharp triangle, and as the fill spacing gradually decreases, the bottom residue also decreases.)
[0087] S132 determines the scanning speed: Assuming the spot diameter is D1 (0.04 mm), the laser frequency is F (60 kHz), and the scanning speed is V (500 mm / s), the overlap rate is calculated to be 80%. (Overlap rate R = 1 - V / D1 F, the scanning speed V is determined by calculation).
[0088] S133 determines the switch optical delay: The switch optical delay setting value is 50ms.
[0089] S134 Define the fill pattern: Select parallel line fill. (Several fill patterns are available, including grid, parallel lines, and webbing.)
[0090] S135 Determines the fill direction: Select fill direction 0 degrees, bow-shaped fill. (Fill direction options include 0-90 degrees, sequential fill, and bow-shaped fill)
[0091] S136 Sample Fabrication: According to the parameters set in S131-S136, fabricate several 25*25mm samples for the next step, Step 14, testing.
[0092] Step 14 Second Scan
[0093] S141 determines the secondary scan linewidth and power: Keeping all other parameters unchanged, set the fill distance to D1 / 2 (0.02mm), D1 / 2+0.005mm (0.025mm), D1 / 2-0.005mm (0.015mm), D1 / 2+0.01mm (0.03mm), D1 / 2-0.01mm (0.01mm), D1 / 2+0.015mm (0.035mm), and D1 / 2-0.015mm (0.005mm). The laser power is equal to W1 / 2, W1 / 2+5%, W1 / 2-5%, W1 / 2+10%, W1 / 2-10%, the filling direction is 90 degrees, and the filling is in an arc shape. Take a sample of S136 and make a 5*5mm sample on the sample. Use a microscope to check the roughness of the sample. Select the sample with the lowest roughness. The filling distance corresponding to the sample is the secondary scan linewidth D2, and the corresponding laser power is the secondary scan power W2. D2 is D1 / 2+0.005mm, that is, 0.025mm; W2 is W1 / 2.
[0094] S142 Sample Fabrication: Based on the secondary scan line width D2 and secondary scan power W2 parameters determined in S141, perform secondary scanning on the remaining samples obtained in S136 to fabricate 25*25mm samples for the next step, Step 2 testing.
[0095] Step 2: Aluminum material planarization. The process flow is as follows: Figure 5 As shown:
[0096] S21 Focus
[0097] S211 Back focal focusing: Take one sample from S142 and place it on the processing platform 11, set the scanning speed to 10mm / s, draw a set of line segments for continuous scanning, adjust the lifting mechanism 24 to make the laser processing assembly 20 descend continuously, and record the coordinate point where the sample shows the strongest flash as the back focal coordinate Z1.
[0098] S212 Front focal focusing: Adjust the lifting mechanism 24 to make the laser processing assembly 20 continue to descend, the flash of the sample weakens, and continue to descend to the second coordinate point with the strongest flash, which is recorded as the front focal coordinate Z2.
[0099] S213 Homogenization plane focusing: Adjust the coordinate of the laser processing assembly 20 to the exact middle position between Z1 and Z2, which is the homogenization plane.
[0100] S22 Line scribing: Set the pulse width of the fiber laser to 1ns, in continuous laser mode; set the scanning speed to 500mm / s, then sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, to scribe 20 lines.
[0101] S23 Detection: Use a confocal microscope to sequentially measure the line width and scribing depth of each scribed line.
[0102] S24 Preliminary determination of line width and power: Select the scribed lines that are completely melted, have no further increase in width, and have no heat-affected zone, then further screen out the scribed lines with smooth surface and no burst points, and the line width and power corresponding to this scribed line are the preliminarily determined line width D and power W, where D is 0.04mm and W is 40%.
[0103] S25 Making small samples: Set the scanning speed to 500mm / s, the filling pitches are respectively D / 2 (i.e. 0.02mm), D / 2+0.005mm (i.e. 0.025mm), D / 2-0.005mm (i.e. 0.015mm), D / 2+0.01mm (i.e. 0.03mm), D / 2-0.01mm (i.e. 0.01mm), D / 2+0.015mm (i.e. 0.035mm), D / 2-0.015mm (i.e. 0.005mm), the powers are respectively W, W+5%, W-5%, W+10%, W-10%, the filling mode is grid, and 5*5mm small samples are made on several samples obtained in S142.
[0104] S26 Confirmation
[0105] S261 Short circuit test: Use the multimeter range, and the small sample is qualified if the multimeter emits a "beep" sound.
[0106] S262 Observation: Observe and examine the samples using a confocal microscope, and select the sample with the lowest roughness. The corresponding filling spacing and power parameters are the optimal parameters D3 and W3; D3 is D / 2+0.005mm (i.e. 0.025mm), and W3 is W+5%.
[0107] S27 Sample Fabrication: Based on the optimal parameters D3 and W3 confirmed in S262, fabricate a 25*25mm aluminum flattening sample on the remaining samples obtained in S142 for the next step, Step 3 test.
[0108] Step 3: Laser high-gloss polishing. The process flow is as follows: Figure 6 As shown:
[0109] S31 Focusing: Take one sample from S27 and place it on the processing platform 11. Adjust the lifting mechanism to move the laser processing component to the back focal coordinate Z1.
[0110] S32 Polishing: Set the pulse width to PW (1ns), the scan speed to 500mm / s, the fill spacing to D1 / 2 (i.e., 0.02mm), the fill mode to bow-shaped, and the fill direction to 0 degrees; sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, and 100%, and create 20 5*5 polishing samples.
[0111] S33 Detection
[0112] S331 Observation: Observe and use a confocal microscope to examine the samples, and select several samples with relatively low roughness.
[0113] S332 Gloss Measurement: Use a gloss meter to measure the selected samples. The power corresponding to the sample with the highest GU value is the optimal first polishing power W4, where W4 is 40% of the set power.
[0114] S34 Sample Fabrication: Take multiple S27 samples, set the power to W4, and keep other parameters the same as in step S32. Fabricate 25*25mm sample pieces on the S27 samples.
[0115] S35 Second Polishing: Set the scanning speed to 500mm / s, the filling distances to D1 / 2, D1 / 2±0.005mm, D1 / 2±0.01mm, and D1 / 2±0.015mm, the filling pattern to bow shape, the filling direction to 90 degrees, and the power to 2*W4, 2*W4+5%, 2*W4-5%, 2*W4+10%, and 2*W4-10%, respectively, and make 5*5mm polishing samples in sequence.
[0116] S36 Confirmation Parameters
[0117] S361 Observation: Observe and inspect the polished samples using a confocal microscope, and select several samples with relatively low roughness therefrom.
[0118] S362 Gloss measurement: Measure the selected samples above with a gloss meter, and the filling distance and power corresponding to the sample with the maximum GU value are the optimal filling distance parameter D5 and the optimal power parameter W5, where D5 is D1 / 2+0.005, that is, 0.025mm, and W5 is 70%.
[0119] S363 Short circuit test: Use a multimeter range, it is qualified if the measured resistance of the sample is infinite and no "beep" sound is emitted.
[0120] S37 Sample preparation: Prepare 10 formal samples according to all the procedures from S11 to S36 described above, check the reproducibility of the parameters, and archive the samples. After testing, the polished surface roughness of the above alloy material samples can all reach below 0.4μm, and the surface gloss can reach above 400GU.
[0121] The polishing effects of the laser polishing apparatus in this embodiment under different commissioning parameters are as Figure 7 shown, wherein the area A is the polished sample finally manufactured by the commissioning method of this embodiment, which has a surface roughness of 0.3μm and a surface gloss of 450GU.
[0122] The above description is merely a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and all such modifications or substitutions shall be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the appended claims.
Claims
1. A method for adjusting a laser polishing device for high-gloss polishing of aluminum alloys, the laser polishing device comprising a fiber laser, a lifting mechanism, a laser processing assembly, and a processing platform; the laser processing assembly comprising a laser output head, a beam expander, a DOE (Displacement Optical Array), and a galvanometer assembly; the fiber laser being modulated into both pulsed and continuous laser modes, and outputting Gaussian laser light from the laser output head; the Gaussian laser light being expanded, shaped, and scanned and focused sequentially by the beam expander, DOE, and galvanometer assembly before irradiating the processing platform; the laser processing assembly being mounted on the lifting mechanism, which is used to adjust the vertical movement of the laser processing assembly; the processing platform being located below the galvanometer assembly; characterized in that... Includes the following steps: Step 1: Remove the anodic oxide layer Step 11: Detect the thickness of the oxide layer; Step 12 Determine the parameters of the anode-breaking laser. S121 Focusing: Place the aluminum alloy sample on the processing platform and adjust the lifting mechanism to move the laser processing component to the front focal coordinate or the rear focal coordinate. S122 Frequency Setting: Refer to the waveform diagram of the laser and set the frequency F corresponding to the highest power. S123 Pulse Width Setting: Refer to the laser parameter table to set the pulse width PW corresponding to the frequency F; S124 scribing: Set the scanning speed to any value between 100-500mm / s, and then set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% in sequence, with 20 scribing lines; S125 Inspection: Measure the line width and depth of each engraving line in sequence; S126 Determine line width and power: First, screen out lines whose width no longer changes and have no heat-affected zone. Then, screen out lines whose depth just exceeds the oxide layer thickness. The line width and power corresponding to this line are the optimal line width D1 and power W1. Step 13 Determine the scanning parameters S131 Determine the fill spacing: Determine the fill spacing as D1 / 2; S132 Determine the scanning speed: Let the spot diameter be D1, the laser frequency be F, the scanning speed be V, and the overlap rate be R; the overlap rate R = 1 - V / D1 * F, take R ≥ 80%, and determine the scanning speed V = (1 - R) * D1 * F by calculation; S133 determines the switch optical delay: the switch optical delay setting value is 0-100ms; S134 Define the fill pattern: Select parallel line fill; S135 determines the fill direction: Select 0 degrees, bow-shaped fill; S136 Sample Fabrication: According to the parameters set in S131-S136, fabricate several 25*25mm samples for the next step, Step 14, testing. Step 14 Second Scan S141 Determine the secondary scan linewidth and power: Keeping other parameters unchanged, set the filling distance to D1 / 2, D1 / 2±0.005mm, D1 / 2±0.01mm, and D1 / 2±0.015mm respectively, the laser power to W1 / 2, W1 / 2±5%, and W1 / 2±10%, the filling direction to 90 degrees, and the filling in an arc shape. Take a sample from S136 and make a 5*5mm sample on it. Use a microscope to check the roughness of the sample and determine that the filling distance corresponding to the sample with the lowest roughness is the secondary scan linewidth D2 and the corresponding laser power is the secondary scan power W2. S142 Sample fabrication: Based on the secondary scan line width D2 and secondary scan power W2 parameters determined in S141, perform secondary scanning on the remaining samples obtained in S136 to fabricate 25*25mm samples for the next step Step2 test. Step 2: Aluminum Material Planarization S21 focuses; adjust the lifting mechanism to move the laser processing component to the exact midpoint between the front and rear focal coordinates; S22 Grating: Set the fiber laser pulse width to 1ns, continuous laser mode; set the scanning speed to any value between 100-500mm / s, and then sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 20 graffito lines; S23 Inspection: Measure the line width and depth of each engraving line in sequence; S24 Initial determination of line width and power: Select lines where all the lines are melted, the width no longer increases, and there is no heat-affected zone. Then, select lines with smooth surfaces and no burst points. The line width and power corresponding to these lines are the initial determination of line width D and power W. S25. Make a small sample: Keep the scanning speed set in step S22 unchanged, set the fill spacing to D / 2, D / 2±0.005mm, D / 2±0.01mm, D / 2±0.015mm, and the power to W, W±5% and W±10%, respectively. Set the fill mode to grid and make a 5*5mm small sample on the samples obtained in S142. S26 Confirmation parameters: Use a confocal microscope to examine the samples and select the sample with the lowest roughness. The corresponding filling spacing and power parameters are the optimal parameters D3 and W3. S27 Sample Fabrication: Based on the optimal parameters D3 and W3 confirmed in S26, fabricate a 25*25mm aluminum flattening sample on the remaining samples obtained in S142 for the next step, Step 3 test. Step 3: Laser High-Gloss Polishing S31 Focusing: Take a sample of S27 and place it on the processing platform. Adjust the lifting mechanism to move the laser processing component to the front focal coordinate or the rear focal coordinate. S32 Polishing: Set the pulse width to PW, the scanning speed to any value between 100-500mm / s, the fill spacing to D1 / 2, the fill pattern to bow-shaped, and the fill direction to 0 degrees; sequentially set the power to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or until the scanning burst point, and sequentially produce ≤20 5*5 polishing samples; S33 Detection S331 Observation: Observe and examine the samples using a confocal microscope, and select several samples with relatively low roughness. S332 Gloss Measurement: Use a gloss meter to measure the selected samples above. The power corresponding to the sample with the highest GU value is the optimal first polishing power W4. S34 Sample Fabrication: Take multiple S27 samples, set the power to W4, and keep other parameters the same as in step S32. Fabricate 25*25mm sample pieces on the S27 samples. S35 Second Polishing: Set the scanning speed to be the same as in step S32, and the filling distances to D1 / 2, D1 / 2±0.005mm, D1 / 2±0.01mm, and D1 / 2±0.015mm respectively. The filling mode is bow-shaped, the filling direction is 90 degrees, and the power is 2*W4, 2*W4±5%, and 2*W4±10% respectively. Make 5*5mm polishing samples on the intermediate sample in sequence. S36 Confirmation Parameters S361 Observation: Observe and examine the polished samples using a confocal microscope, and select several samples with relatively low roughness. S362 Gloss Measurement: Use a gloss meter to measure the selected samples above. The fill distance and power corresponding to the sample with the highest GU value are the optimal fill distance parameter D5 and the optimal power parameter W5. S37 Sample Production: Produce multiple standard samples following the entire process described in S11-S36 above, check the reproducibility of parameters, and archive the samples.
2. The debugging method according to claim 1, characterized in that, Step 11, which involves detecting the oxide layer thickness, specifically involves using an eddy current film thickness tester to detect the oxide layer thickness. There are at least five detection points, which are distributed around the periphery and center of the workpiece. The maximum detected thickness is taken as the oxide layer thickness.
3. The debugging method according to claim 1, characterized in that, In Step 121, adjusting the lifting mechanism to move the laser processing component to the front focal coordinate or the back focal coordinate is specifically as follows: the fiber laser is set to a scanning speed of any value between 1 and 10 mm / s, and emits laser light for continuous scanning. At the same time, the lifting mechanism is adjusted to drive the laser processing component to continuously descend from the highest position. The coordinate point of the laser processing component when the laser flashes most intensely on the sample is recorded as the back focal coordinate, and the coordinate point of the laser processing component when the laser flashes most intensely on the sample is recorded as the front focal coordinate.
4. The debugging method according to claim 1, characterized in that, In the above S26, before testing the sample with a confocal microscope, the step of using a multimeter " " range to test for short circuits is further included, and the sample is qualified if it emits a "beep" sound.
5. The debugging method according to claim 1, characterized in that, After the described S362, the method further includes S363 short circuit testing: using the multimeter " " range, testing that the resistance of the sample is infinite and no "beep" sound is emitted is qualified.
6. The debugging method according to claim 1, characterized in that, The fiber laser mentioned is a fiber infrared MOPA single-mode laser.
7. The debugging method according to claim 1, characterized in that, The fiber laser mentioned is a 50-500W fiber laser.
8. The debugging method according to claim 1, characterized in that, The focal length of the galvanometer is 100-260mm.
9. The debugging method according to claim 1, characterized in that, The laser polishing device also includes a base; the lifting mechanism and processing platform are mounted on the base.
Citation Information
Patent Citations
Laser marking method and device for high-brightness machining of aluminum alloy
CN113458611A
Continuous pulse-switchable intermediate-infrared fiber laser
CN106340796A
Double-beam laser polishing equipment and polishing method for aluminum alloy
CN113290319A
Laser scanning processing system and method
CN116626905A